The Omental Free Flap—A Review of Usage and Physiology - Mazzaferro, Daniel; Song, Ping; Massand, Sameer; Mirmanesh, Michael; Jaiswal, Rohit; Pu, Lee L. Q. (Journal of Reconstructive Microsurgery, 2018)
Background The omental flap has a rich history of use over the last century, and specifically as a free flap in the last four decades. It has a wide variety of applications in reconstructive surgery and has shown itself to be a reliable donor tissue. We seek to review the properties that make the omental free flap a valuable tool in reconstruction, as well as its many surgical applications in all anatomic regions of the body.Methods We conducted a narrative review of the literature on Medline and Google Scholar. We reviewed basic science articles discussing the intrinsic properties of omental tissue, along with clinical papers describing its applications.Results The omental free flap is anatomically suitable for harvest and wound coverage and has molecular properties that promote healing and improve function at recipient sites. It has demonstrated utility in a wide variety of reconstructive procedures spanning the head and neck, extremities, and viscera and for several purposes, including wound coverage, lymphedema treatment, and vascularization. It is also occasionally employed in the thoracic cavity and chest wall, though more often as a pedicled flap. More novel uses include its use for cerebrospinal fluid leaks.Conclusions The omental free flap is a valuable option for reconstructive efforts in nearly all anatomic regions. This is a result of its inherent anatomy and vascularity, and its angiogenic, immunogenic, and lymphatic properties.
Keywords: omentum; free flap; omental flap